2022
DOI: 10.1093/brain/awac154
|View full text |Cite
|
Sign up to set email alerts
|

Mutations inTAF8cause a neurodegenerative disorder

Abstract: TAF8 is part of the transcription factor II D complex, composed of the TATA-binding protein and 13 TATA-binding protein–associated factors (TAFs). Transcription factor II D is the first general transcription factor recruited at promoters to assemble the RNA polymerase II preinitiation complex. So far disorders related to variants in 5 of the 13 subunits of human transcription factor II D have been described. Recently, a child with a homozygous c.781-1G>A mutation in TAF8 has been reported. Here we descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In conclusion, our study supports the vision of a much more dynamic and flexible Pol II transcription initiation machinery. Interestingly, this flexibility has some impact on human physiopathology as a growing number of mutations have been identified in TAF1 , TAF2 , TAF4 , TAF6 , TAF8 and TAF13 genes, in patients associated with neurodevelopmental defects and intellectual disabilities 58,77,78 . Surprisingly, these mutations mainly affect the brain development and function but without any major effect on the other organs, clearly suggesting that the transcription initiation machinery has a certain degree of adaptability but that the cellular context is a main constraint.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our study supports the vision of a much more dynamic and flexible Pol II transcription initiation machinery. Interestingly, this flexibility has some impact on human physiopathology as a growing number of mutations have been identified in TAF1 , TAF2 , TAF4 , TAF6 , TAF8 and TAF13 genes, in patients associated with neurodevelopmental defects and intellectual disabilities 58,77,78 . Surprisingly, these mutations mainly affect the brain development and function but without any major effect on the other organs, clearly suggesting that the transcription initiation machinery has a certain degree of adaptability but that the cellular context is a main constraint.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, TAF8 has been linked to neurodegenerative disorders characterized by hypomyelination, a thin corpus callosum, and brain atrophy (Wong et al, 2022). Such alterations are associated with heterozygosity for several gene variants, including the intronic TAF8 variant GRCh38:chr6:g.42050590A>G and the exonic TAF8 variant GRCh38:chr6:g.42057513G > A (Wong et al, 2022).…”
Section: Cell Differentiation and The Role Of Tafs In The Regulation ...mentioning
confidence: 99%
“…Finally, TAF8 has been linked to neurodegenerative disorders characterized by hypomyelination, a thin corpus callosum, and brain atrophy (Wong et al, 2022). Such alterations are associated with heterozygosity for several gene variants, including the intronic TAF8 variant GRCh38:chr6:g.42050590A>G and the exonic TAF8 variant GRCh38:chr6:g.42057513G > A (Wong et al, 2022). It has been reported that TAF8 is an integral subunit of the functionally active TFIID, essential for integrating TAF10, an action mediated by its histone‐fold domain (Guermah et al, 2003).…”
Section: Cell Differentiation and The Role Of Tafs In The Regulation ...mentioning
confidence: 99%